STUDI TIMBULAN DAN KOMPOSISI SAMPAH PERKOTAAN DI KELURAHAN BANYUNING - Putu Indra Christiawan; I Putu Ananda Citra (Universitas Pendidikan Ganesha, 2016)
Banyuning Sub-district is part of the city of Singaraja potentially having problems of urban waste. This fact is supported by the existence of settlements, especially the residential as the largest land use in Banyuning Sub-district. The existence of residential, both public housing and housing of BTN indirectly contribute greatly to the amount of waste generated and variations in the composition of waste being generated. Based on this phenomenon, this study has the objective to: (1) analyze the characteristics of the waste generated in the residential in Banyuning Sub-district and (2) analyze the characteristics of the waste composition of the residential in the Banyuning Sub-district. The method used in achieving the goals of this research is analytic survey with the settler population is a residential. This analytic survey research using a sample area with a purposive sampling techniques, and using proportional random sampling technique to take a sample of the subject in each residential which is used as a sample area. The analysis used in this research is descriptivestatistics. Descriptive statistical analysis is used to describe the characteristics of the settlers as well as waste generation and waste composition. The technique of collecting data through questionnaires and observation in accordance with SNI 19-3964-1994 about the sampling method and measurement examples of the composition and urban waste. Mapping on the distribution characteristics of waste generation and waste composition is the result of research obtained to understand the characteristics of most large waste produced by the settlers in the residential in the Banyuning Sub-district. Key words: Waste Generation, Waste Composition